What lies downstream: Cellular oxygen delivery during hemodialysis. Issue 3 (4th December 2018) - MacEwen, Clare; Watkinson, Peter; Tarassenko, Lionel; Pugh, Christopher
Abstract: Hemodialysis has been linked to structural and functional damage to vital organs such as the brain and heart, possibly via repetitive intradialytic organ ischemia. There is increasing recognition that tissue ischemia can occur without changes in standard hemodynamic parameters such as blood pressure, leading to interest in more direct assessment of the adequacy of oxygen delivery to tissues. In this article, we discuss our current understanding of what happens to cellular oxygen delivery during hemodialysis: we review the underlying physiology, potential measurement techniques, and the clinical literature to date.